Inelastic cross sections in relativistic deuterons on Lead reactions - Zamani, M.; Stoulos, S.; Fragopoulou, M.; Krivopustov, M. (HNPS Advances in Nuclear Physics, 2020)
The inelastic cross section of deuterons hitting a Lead target has been determined by the beam attenuation technique. A spallation neutron source based on Lead target has been irradiated with 1.6 and 2.5 GeV deuterons. Solid state nuclear track detectors as well as the activation method were used in order to obtain the neutron and proton distribution along the surface of the source. The attenuation coefficient was estimated by fitting the experimental data taking into account the build up effect and the beam attenuation. Using the attenuation coefficient, the interaction length and then the inelastic cross section of deuterons on Lead reaction have been determined.